Being Smart Is Not Enough: Personality Traits and Vocational Interests Incrementally Predict Intention, Status and Success of Leaders and Entrepreneurs Beyond Cognitive Ability - Bergner, Sabine (Frontiers in Psychology, 2020)
Three separate studies demonstrate that socio-emotional skills add incremental validity beyond cognitive ability when predicting leadership and entrepreneurship intention, emergence as well as success. Study 1 uses a longitudinal approach and tests the cognitive ability and vocational interests of 231 students to predict their leadership and entrepreneurship intention. It demonstrates that cognitive ability predicts their intention to become a business leader or entrepreneur two years in the future. Importantly, the vocational interests “enterprising” and “social” increase this ability-driven prediction of leadership and entrepreneurship intention (∆R²Lead. Intent. =15%, ∆R² Entre. Intent. = 9%). Study 2 investigates 123 business leaders and shows that those with higher cognitive ability more likely emerge as top-level leaders, receive more income and get slightly better supervisor-ratings on their performance. The leaders’ Big Five traits (openness, conscientiousness, extraversion, agreeableness, emotional stability) added validity beyond cognitive ability when predicting these criteria (∆R²Income = 9%, ∆R²Lead. Level = 8%, ∆R²Perform. = 15%). Finally, Study 3 includes 155 participants and demonstrates that cognitive ability predicts a person’s entrepreneurial status but not performance. Additionally, considering the Big Five traits improves the prediction of who becomes an entrepreneur and successfully performs as such (∆R²Status = 7%, ∆R²Perform. = 18%). Importantly, selected Big Five traits and vocational interests boost the importance of cognitive ability in the field of leadership and entrepreneurship. Concluding, this series of studies suggests that it is the combination of personality traits or interests with cognitive ability which is most powerful when predicting leadership and entrepreneurship intention, emergence and success.